Preservation and adaptation: a qualitative comparison of Japanese and Dutch kendo instructors - Boomgaard, Pepijn; Kawashima, Kohei (Frontiers in Sports and Active Living, 2025)
IntroductionKendo, a Japanese martial art rooted in traditional swordsmanship, has spread internationally. The art maintains strong cultural ties to Japan. As the global practitioner base expands, questions arise about how kendo is adapted in different cultural contexts and to what extent its original values and traditions are preserved. This qualitative study explored how cultural background influences kendo instruction by comparing the perspectives of Japanese and Dutch kendo instructors.MethodTen experienced kendo instructors from Japan and the Netherlands participated in semi-structured interviews. Data were analyzed using reflexive thematic analysis. Hofstede's cultural dimensions theory served as the analytical framework for interpreting the influence of national culture on instructors’ teaching approaches.ResultsJapanese instructors emphasized competitive success, hierarchical relationships, and student creativity, reflecting cultural values of masculinity and high power distance, while also subverting expectations regarding individualism. In contrast, Dutch instructors promoted recreational practice and egalitarian relationships, and reported challenges with overly critical students. These findings mirror cultural tendencies of femininity and low power distance, but defy assumptions regarding individualism. Despite these differences, both groups showed a strong commitment to preserving kendo's traditional values.DiscussionThe findings suggest that while instructional styles vary by culture, kendo's traditional principles are maintained across borders. Instructors play a key role in negotiating the balance between cultural adaptation and the preservation of kendo's identity. This study contributes to understanding the cross-cultural transmission of martial arts and highlights the need for further research including student perspectives and other national contexts.